Factors associated with time to first dialysis-associated peritonitis episode: Data from the Peritonitis Prevention Study (PEPS). Issue 3 (May 2023) - Ljungman, Susanne; Jensen, Jørgen E; Paulsen, Dag; Petersons, Aivars; Ots-Rosenberg, Mai; Saha, Heikki; Struijk, Dirk; Wilkie, Martin; Heimbürger, Olof; Stegmayr, Bernd; Elung-Jensen, Thomas; Johansson, Ann-Cathrine; et al.
Introduction: Peritonitis remains a potentially serious complication of peritoneal dialysis (PD) treatment. It is therefore important to identify risk factors in order to reduce the incidence of peritonitis. The aim of the present analysis was to identify factors associated with time to first peritonitis episode. Methods: Incident PD patients from 57 centres in Europe participated in the prospective randomised controlled Peritonitis Prevention Study (PEPS) from 2010 to 2015. Peritonitis-free, self-care PD patients ≥18 years were randomised to a retraining or a control group and followed for 1–36 months after PD initiation. The association of biochemical, clinical and prescription data with time to first peritonitis episode was studied. Results: A first peritonitis episode was experienced by 33% (223/671) of participants. Univariable Cox proportional hazard regression showed a strong association between the time-updated number of PD bags connected per 24 h (PD bags/24 h) and time to first peritonitis episode (HR 1.35; 95% confidence interval (CI) 1.17–1.57), even after inclusion of PD modalities in the same model. Multivariable Cox regression revealed that the factors independently associated with time to first peritonitis episode included age (HR 1.16 per 10 years; 95% CI 1.05–1.28), PD bags/24 h (HR 1.32; 95% CI 1.13–1.54), serum albumin <35 versus> 35 g/L (HR 1.39; 95% CI 1.06–1.82) and body weight per 10 kg (HR 1.10; 95% CI 1.01–1.19). Conclusion: This study of incident PD patients indicates that older age, greater number of PD bags connected/24 h, higher body weight and hypoalbuminaemia are independently associated with a shorter time to first peritonitis episode.